A Multi-State Analysis of Early-Term Delivery Trends and the Association With Term Stillbirth. Issue 6 (December 2015) - Little, Sarah E.; Zera, Chloe A.; Clapp, Mark A.; Wilkins-Haug, Louise; Robinson, Julian N.
Abstract : OBJECTIVE: To investigate whether reduction in early-term deliveries was associated with increasing rates of term stillbirth. METHODS: This is a retrospective descriptive analysis of variation in term delivery timing and stillbirth from 2005 to 2011 based on birth certificate and fetal death data. Early-term deliveries (37 0/7–38 6/7 weeks of gestation) as a percentage of total term delivery and term stillbirth rates were calculated for each state, both overall and for low- and high-risk women. We analyzed whether state-level changes in early-term deliveries and term stillbirth were correlated using Pearson correlation coefficients. States were also categorized as high or low reduction (above or below the national average) and changes in stillbirth rates for these groups were analyzed using a Cochrane-Armitage test for linear trend. RESULTS: There was a decline in early-term deliveries across the United States: 1, 123, 467 of 3, 533, 233 term, singleton births occurred in the early term in 2005 (31.8%) as compared with 978, 294 of 3, 429, 172 (28.5%) in 2011. Reductions varied widely by state. There was no change in the term stillbirth rate (123/100, 000 births in 2005 compared with 130/100, 000 in 2011; P =.189) nor change in the high reduction states alone. There was no correlation between state-level changes in early-term deliveries and term stillbirth. There was an increase in term stillbirths among women with diabetes (from 238/100, 000 to 300/100, 000 births; P =.010), independent of changes in early-term delivery timing. CONCLUSION: The reduction in early-term deliveries across the United States between 2005 and 2011 was not associated with an increase in the rate of term stillbirth. LEVEL OF EVIDENCE: II Abstract : Supplemental Digital Content is Available in the Text.Between 2005 and 2011, early-term delivery declined in the United States; this finding is not associated with changes in term stillbirth rates at a state level.